اختبار ملاءمة قيمة الأرباح المحاسبية والقيمة الدفترية للسهمفي سوق دمشق للأوراق المالية - الطويل ليلى; شاهين سوسن (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تختبر هذه الدراسة ملاءمة قيمة المعلومات المحاسبية المتمثلة بالأرباح والقيم الدفترية للشركات المدرجة في سوق دمشق للأوراق المالية. تعتمد الدراسة على نموذج العائد المطور من قبل Easton & Harris (1991)، وعلى نموذج السعر المطور من قبل Ohlson (1995) باستخدام بيانات القوائم المالية السنوية خلال الفترة الممتدة من 2009-2012.تظهر نتائج الدراسة بأن الأرباح المحاسبية ملائمة القيمة لتفسير التغيرات في عوائد الأسهم وبأن متغير التغير في الأرباح يرتبط إيجابياً وبشكل معنوي مع عوائد الأسهم، أما متغير مستوى الأرباح لا يرتبط معنوياً مع العائد المتراكم. ووفق نموذج السعر فإن ربحية كل سهم وقيمته الدفترية ترتبطان إيجابياً وبشكل معنوي مع سعر السهم، لذلك فإن قائمة الدخل والميزانية العمومية تعكسان معلومات ملائمة القيمة للمستثمرين في سوق دمشق للأوراق المالية، وتتمثل هذه المعلومات بالأرباح والقيم الدفترية، إلا أن متغير مستوى الأرباح في نموذج العائد لا يفسر التغيرات في العائد المتراكم. This study examines the relevance-value of accounting information represented by earnings and book values for firms listed on Damascus Stock Exchange. This study is based on the Return Model developed by Easton & Harris (1991), and on the Price Model developed by Ohlson (1995).The researcher uses the annual data of the financial statements from 2009 to 2012. The results of this study show that accounting earnings are value-relevant to explaining the changes in stock returns, and that the change-variable in earnings correlates positively and significantly with cumulative return, but earnings level variable does not related significantly to cumulative returns. Based on the price model, the earnings of each share and its book-value relate positively and significantly to share-price. Therefore, income statements and balance sheets reflect value-relevant information for investors at Damascus Stock Exchange. This information is represented by accounting earnings and book values, but the variable of earnings level does not explain the changes in cumulative returns.